Residential AC Technician Competency Training and Certification (Level 3) in Pekanbaru - Brian Agung Cahyo P.; Sunny Ineza Putri; Jheri Hermanto; Anita Susilawati; Dedy Masnur; Dodi Sofyan Arief; Putri Nawangsari; Annisa Wulan Sari; Mintarto .; Hanif Nugroho Aji; Rahmatsyah Maksum Ramsi (Faculty of Engineering UNHAS, 2026)
This Community Service Activity by the Mechanical Engineering Department of Riau University was a strategic move to address the urgent need for the formalization and quality improvement of Air Conditioner (AC) technicians. The program was based on the official appointment of Mechanical Engineering Unri as a Temporary Competency Test Center by a credible Professional Certification Body (LSP), affirming the institution's role in implementing the National Work Competency Standards (SKKNI). Targeting technicians with a minimum of one year of experience, the program had a dual objective: validating the existing practical skills while enhancing knowledge on crucial aspects like Occupational Health and Safety (K3) and environmentally compliant refrigerant handling. The PKM was implemented through structured stages, commencing with strict recruitment and selection, followed by comprehensive training delivered by Unri's competent lecturers, focusing on core competency units. The culmination was the Competency Test, conducted independently by certified Assessors from the partner LSP at the Unri TUK. The assessors evaluated participants' knowledge, skills, and work attitude through written, oral, and practical examinations. The main outcome of this activity was the successful certification of professional technicians. A total of 10 (ten) AC technicians were declared Competent and officially received the AC Technician Professional Competency Certificate from BNSP. This achievement significantly contributes to upgrading the quality and competitiveness of the local workforce, boosting professionalism, service quality, and career prospects for the certified technicians.